Older Low-Efficient Boilers Brown Coal-Fired, Generated Emissions and Diffusion of Imissions - Jozef Blaho; Jozef Víglasky; Peter Horbaj (Communications - Scientific letters of the University of Zilina, 2006)
At thermooxidizing processes generating energy from natural solid fuels, heat as its main product is accompanied with side products – solid waste and emissions, resulting in unfavourable effects on the environment. This contribution deals with the results of measurements and analyses regarding an old-fashioned type boiler unit fired by solid fuel. It showed low efficiency of older brown coal fired boilers currently used in many small companies. All of them generate pollutants – gaseous as well as solid emissions polluting the environment. Thus, they cause environmental damage in spite of their meeting emission and imission limits within their category. The imission value of tar component at low temperature of flue gases in fireplace and short time of flue gas remaining in fireplaces causes the presence of some components over the permissible imission limit.